2019
DOI: 10.1167/iovs.19-27200
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin Use for Multi-Drug Resistant Pseudomonas aeruginosa: In Vitro and In Vivo Studies

Abstract: PURPOSE.Our purpose was to test glycyrrhizin (GLY) effects and ciprofloxacin interactions on multidrug resistant (MDR) isolates of Pseudomonas aeruginosa in vitro and in vivo in a mouse model of keratitis. METHODS.A Hardy-disk tested antibiotic sensitivity of isolates MDR9 (nonocular) and B1045 (ocular). GLY MIC (both isolates) and ciprofloxacin was determined spectrophotometrically. A live/dead assay using confocal microscopy and plate count, tested GLY effects on bacterial permeabilization/viability. Proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Glycyrrhetinic acid is considered the major active component of G. glabra root extract, which may contain about 2-25% glycyrrhetinic acid, both as such and as the glycosidic glycyrrhizinic acid saponin [23]. In humans, it is in fact known that after oral administration, glycyrrhizinic acid is hydrolysed to glycyrrhetinic acid mainly by the intestinal bacteria b-D-glucuronidase [20,40].…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhetinic acid is considered the major active component of G. glabra root extract, which may contain about 2-25% glycyrrhetinic acid, both as such and as the glycosidic glycyrrhizinic acid saponin [23]. In humans, it is in fact known that after oral administration, glycyrrhizinic acid is hydrolysed to glycyrrhetinic acid mainly by the intestinal bacteria b-D-glucuronidase [20,40].…”
Section: Discussionmentioning
confidence: 99%
“…GLY had a minimum inhibitory concentration (MIC) of 40 mg/mL for each of the clinical isolates as well as two lab strains (PAO1 and 19660) tested [8,19,20]. The MIC of multi-drug resistant strain MDR9, isolated from sputum also was 40 mg/mL, but MIC was reduced to 15 mg/mL for the ocular isolate B1045 [21], suggesting that GLY may not affect all MDR similarly.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies from our laboratory, including a proteomic comparison of RS1 (a non-ocular, drug resistant clinical isolate) and PAO1 showed that the gene ampC, which is responsible for beta lactamase production, was detectable in RS1 but not PAO1 [20]. Additional studies showed GLY treatment had an effect on other intrinsic resistance mechanisms, namely increase in membrane permeability in MDR9 and significant reduction in expression of major resistance-nodulation-division (RND) efflux pump genes in both MDR9 and B1045 [21]. Combined with the finding that GLY reduces beta-lactamase in MDR9, but not B1045, the premise that GLY can alter multi-drug resistant mechanisms differentially between isolates appears supportable.…”
Section: Discussionmentioning
confidence: 99%
“…( Ashfaq et al, 2017 , Omar et al, 2012 , Oyama et al, 2016 , Soufy et al, 2012 , Bailly and Vergoten, 2020 , Tong et al, 2020 , Velvizhiv and Annapurani, 2018 , Vispute, 2011 , Wang et al, 2015 , Wu et al, 2019 , Xu et al, 2018 , Zakaryan et al, 2017 , Zhang et al, 2018 , Chen et al, 2017 , Dao et al, 2011 , Editorial 2020 , Hazlett et al, 2019 , Aipire et al, 2020b , Hirabayashi et al, 1991 , Kim et al, 2020 , Lee et al, 2018 , Liu et al, 2019 , Liu et al, 2020 , Long et al, 2013 , Maksoud et al, 2019 )…”
Section: Uncited Referencesmentioning
confidence: 99%